Multifunctional Vocational Education(MVE) Curriculum for Vocational Technical Departments of Universities (Experiences Gained During a Fourteen Years Teaching Period in School of Computing and Technology, Eastern Mediterranean University) - İlkan, Mustafa; Çırak, Yeşim (Marmara Üniversitesi Teknik Eğitim Fakültesi, 2005)
[Abstract Not Available]
Keywords: MVE, vocational education, technology